Learning Al-Tibyân Fi Ulûm Al-Qurân Using a Student-Centered Learning Approach at The Al-Bidayah Islamic Boarding School: Pembelajaran Al-Tibyân Fi Ulûm Al-Qurân Menggunakan Pendekatan Student Centered Learning di Pesantren Al-Bidayah - Abdullah Hasyim Zain; ul haqq, Ahmad Dhiyaa (Pesantren Reviews, 2023)
This study aims to provide an overview of learning Al-Tibyân fi Ulûm Al-Qurân with a student-centered learning approach at the Al-Bidayah Islamic Boarding School, Jember. The method used in this research is descriptive qualitative method. The data collection technique of this research used observation, interview, and documentation techniques. The data analysis used in this study is an interactive model data analysis for Miles, Huberman and Saldana namely data collection, data condensation, data presentation and drawing conclusions. In the Al-Tibyân fi Ulûm Al-Qurân learning activities at Al-Bidayah Jember Islamic Boarding School using a student-centered learning approach and collaborating between the discussion method and the lecture method. This student-centered learning approach has succeeded in creating independence in learning and enthusiasm for learning so as to create students who are independent in reading books.